(untitled) (Journal of University of Babylon for Engineering Sciences, 2020)
The reliability of the laboratory tests is the main pillar in the applied side of the quality of the construction projects. The construction materials used in these projects cannot be accepted or rejected until they have passed the laboratory examination according to which these materials are accepted or rejected.. Many organizations have sought to achieve the competitive advantage by providing high quality services through the implementation of the overall quality management standards. It was necessary for the construction laboratories to adopt the quality management method in their work, in particular the application of the standards of ISO 17025: 2005, Which improve the performance of these laboratories in terms of administrative and technical. This research includes a statistical study of a sample of construction laboratories, construction contracting companies and project implementation entities in some government departments to determine the factors affecting the reliability of the laboratory tests. The methodology used in the research will provide recommendations and suggestions to help the laboratory staff focus on the factors influencing the Reliability of tests and handling them according to the ISO 17025: 2005.